Serbuk Dari Limbah Cangkang Telur Ayam Ras Sebagai Adsorben Terhadap Logam Timbal (Pb) - Satriani, Dewi; Ningsih, Purnama; Ratman, Ratman (Jurnal Akademika Kimia, 2016)
The aim of this study is to determine the optimum time and weight required for eggshell powder when it absorbs Pb, and to determine the adsorption capacity of the eggshell powder at the optimum condition for Pb with the shaking time variation of 10, 20, 30, 40 and 50 minutes. The weight variation of adsorbent is 0.25, 0.50, 0.75, 1 and 1.25 grams. The work steps in this study were production of the eggshell powder as the adsorbent, making of a solution of Pb 60 ppm, and determination the Pb concentration at equilibrium using a spectrophotometer spektrodirect respectively. The results obtained after the adsorption process for the time variation was 30 minutes, this optimum time giving %Pb absorbed was 94.65%. The weight variation of adsorbent is 1 gram, this optimum weight giving %Pb absorbedÂ was 98.91%. Furthermore, the absorption capacity adsorbent of eggshell powder in both optimum conditions was 0.078 mg Pb/mg adsorbent.